ALTERNATIF MODEL PENGELOLAAN KEAMANAN DI DAERAH KONFLIK - Sarah Nuraini Siregar (Jurnal Penelitian Politik, 2010)
In Post New Order era the security regulation has been rearranged and has caused a conceptual change ofsecurity and defense in Indonesia This can be seen through the regulation ofseparation ofPolri and ABRI andaccompanied by TAP APR No VI on seperation ofTNI and Polri and TAP MPR VII in 2000 on the role of TNI andPolri These regulations have created a model ofsecurity management which arranged authority between TNI andPolri in conducting security management in conflict areaparticularly in Ambon Poso Aceh and Papua Howeverthese regulations have created new problems in the field especially related to regulation of duty and authoritybetween Polri and TNI in handling security problems in conflict area Based on this illustration this study tries toanalyse the implementation ofstate security managementpolicy in conflict area and to recommend an alternativeofsecurity management model in conflict area along with other operational regulations in order to regulate strictlyand clearly betweenfunction and authority ofTNI and Polri in conducting security management in conflict area